Enhancing the bioavailability of magnolol in rabbits using melting solid dispersion with polyvinylpyrrolidone. (March 2014) - Lin, Shiuan-Pey; Hou, Yu-Chi; Liao, Tzu-Yun; Tsai, Shang-Yuan
Abstract Objective: Preparation of magnolol-loaded amorphous solid dispersion was investigated for improving the bioavailability. Materials and methods: A solid dispersion of magnolol was prepared with polyvinylpyrrolidone K-30 (PVP) by melting method, and the physical properties were characterized by using differential scanning calorimetry, powder X-ray diffractometry, Fourier transformation-infrared spectroscopy and scanning electron microscope. In addition, dissolution test was also performed. Subsequently, the bioavailability of magnolol pure compound, its physical mixture and solid dispersion were compared in rabbits. The blood samples withdrawn via marginal ear vein at specific time points were assayed by HPLC method. Results: Oral administration of the solid dispersion of magnolol with PVP significantly increased the systemic exposures of magnolol and magnolol sulfates/glucuronides by 80.1% and 142.8%, respectively, compared to those given with magnolol pure compound. Conclusion: Magnolol-loaded amorphous solid dispersion with PVP has demonstrated enhanced bioavailability of magnolol in rabbits.